THE MICROPROCESSOR DEVICE FOR MEASUREMENT OF HUMIDITY OF LOOSE MATERIALS - Hulkar Asadullaevna Usmanova; Asadulla Turgunbayev (Web of Journals Publishing, 2024)
The optimal method for creating a universal system for most materials is the ultrahigh-frequency moisture measurement method. The article discusses the generalized structure of a humidity meter. The system is designed to solve all problems related to obtaining measurement information about the moisture content of bulk materials and products of its processing.
Keywords: Optimal method, ultra-high frequency, humidity, sensor, output signals, external device interface.